Design of improved optimal and suboptimal deadlock prevention for flexible manufacturing systems based on place invariant and reachability graph analysis methods. Issue 3 (September 2017) - Pan, Yen-Liang; Tseng, Ching-Yun; Row, Ter-Chan
Flexible manufacturing systems exhibit a high degree of resource sharing. Since the parts advancing through the system compete for a finite number of resources, a deadlock may occur. Accordingly, many pioneers make efforts in the issue. However, how to obtain maximally permissive supervisors in deadlock flexible manufacturing system is an extremely difficult and time-consuming problem. In existing literature, place invariant) and graph analysis method are merged called maximal number of forbidding First Bad Marking (FBM) problem to obtained optimal controllers with a small number of control places. However, this prevention just can be used in some special nets. For general cases, deadlocks could still exist. Therefore, this paper tries to propose one improved iterative deadlock prevention policy to solve above disadvantage. Experimental results show that the proposed improved policy can be used in all kinds of nets. In other words, it does improve the drawback of conventional maximal number of forbidding First Bad Marking (FBM) problem technology.